Dark winds. Season 4 [videorecording (DVD)] - McClarnon, Zahn, 1966-; Gordon, Kiowa, 1990-; Matten, Jessica; Allison, Deanna; Hillerman, Tony (AMC, 2026)
The search for a missing Navajo girl takes Leaphorn, Chee, and Manuelito from the safety of Navajo Nation to the gritty terrain of 1970s Los Angeles in a race against the clock to save her from an obsessive killer with ties to organized crime.